Rumble of the Coaster Ghost: the Notebook of Doom # 9 The Notebook of Doom #9 - Cummings, Troy (New York, NY : Branches/Scholastic, 2016)
Alexander's class is going on a field trip to an amusement park called Safety Land with really slow, boring rides--but this is Stermont, and when a weird magician tells Alexander and his friends that the roller coaster is haunted things start to get a lot more interesting.
Keywords: Monsters -- Juvenile fiction; Roller coasters -- Juvenile fiction; Amusement parks -- Juvenile fiction; School field trips -- Juvenile fiction; Elementary schools -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Fiction; Monsters -- Fiction; Roller coasters -- Fiction; Amusement parks -- Fiction; School field trips -- Fiction; Friendship -- Fiction